A Workshop for Developing Learning Modules for Science Classes Based on Biogeochemical Research. Issue 1 (3rd June 2013) - Harrington, James M.; Gardner, Terrence G.; Amoozegar, Aziz; Andrews, Megan Y.; Rivera, Nelson A.; Duckworth, Owen W.
Abstract : A challenging aspect of educating secondary students is integrating complex scientific concepts related to modern research topics into lesson plans that students can relate to and understand at a basic level. One method of encouraging the achievement of learning outcomes is to use real‐world applications and current research to fuel student interest and excitement. This approach can be reinforced by use of demonstrations, which spur in‐class discussions and can be integrated into out‐of‐class assignments. To attempt to develop improved curricular materials, a workshop was organized that combined the teaching expertise of a number of secondary school teachers with the research experience of a number of scientific experts to produce lesson plans centered around trace metal cycling and toxicity. These areas are important current research topics but are often neglected in pre‐college education. A significant portion of the material presented at the workshop involved the use of visual and hands‐on demonstrations of chemical principles that relate to geochemical processes that impact the environment. Materials provided to the instructors included suggestions for hands‐on, interactive activities for use in the classroom, as well as teacher‐administered demonstrations that would explore the physical and chemical bases of the principles being discussed. The participants all expressed positive feedback in terms of their confidence to administer student‐centered lesson plans on the topic of biogeochemistry and their personal understanding of the subject matter, and a number of lesson plans were developed for use by the teachers to integrate the scientific principles discussed in the body of their courses.